Efficacy of Ampicillin and Gentamycin Combination Therapy in Children Having Severe Acute Malnutrition Presenting with Acute Diarrhea at Civil Hospital Hyderabad (Medical Forum Monthly, 2024)
Objective: To assess the Efficacy of Ampicillin and Gentamycin combination therapy in children having severe acute malnutrition presenting with Acute Diarrhea at Civil Hospital Hyderabad Study Design: Descriptive / case series study Place and Duration of Study: This study was conducted at the Paediatric Department, Liaquat University of Medical and Health Sciences Hospital Hyderabad from 1st July 2017 to 31st December 2017. Materials and Methods: This study was done by Non-probability, consecutive sampling technique in 145 children with the diagnosis of severe under nutrition presenting with acute diarrhea. History and physical examination was carried out. Patients were treated as per the standard guidelines by the WHO and Ampicillin+Gentamycin were given. Weight and height was plotted on the standard growth charts and centiles for age and gender for screening of malnutrition. Results: The average age of the patients was 14.81±7.67 months. Out of 145 under nourished children 85(58.62%) showed satisfactory outcome at the end of 48 hours of therapy Conclusion: In conclusion, treatment with intravenous ampicillin and gentamycin showed improvement in only 58.6% children at the end of 48 hours of therapy. Further large scale studies are needed to review the response of these antibiotics in children having Severe Acute Malnutrition with acute diarrhea, hence to review for any possible change in the current protocol.